Do people with different sociodemographic backgrounds value their health differently? Evaluating the role of positional objectivity - Jyani, Gaurav; Prinja, Shankar; Goyal, Aarti; Garg, Basant; Kaur, Manmeet; Grover, Sandeep (Frontiers in Public Health, 2023)
Objective: The fundamental disconnect between the actual and the perceived health of an individual raises considerable skepticism on the self- reported health data as it may be confounded by an individual’s socio-economic status. In this light, the present study aims to assess if people with different sociodemographic backgrounds value their health differently. Methods: The health-state valuation using time-trade off was performed in a cross-sectional survey among a representative sample of 2311 adults from India. Individuals were selected using a multistage stratified random sampling from five Indian states to elicit their present health-state, and to perform the health-state valuation exercise using computer assisted personal interviewing. A single block of standardized health-states was valued by multiple individuals, each belonging to different socio-demographic group. The difference in the valuation of health was assessed using bivariate analysis. The impact of different sociodemographic factors on the health-state valuation was evaluated using tobit regression model. Results: Differences in the valuation of health were observed among different groups of age, religion, family type, state of residence, substance abuse, presence of ailments at the time of valuation, and number of dependent members in the household. Even after controlling for the severity of the administered health states, factors having a significant association with the valuation of health are age, religion, state of residence, substance abuse, family type, number of dependent members in the household, and presence of chronic or both acute and chronic ailments. Younger individuals place a higher value to their health as compared to their older counterparts. As compared to a healthy individual, a person with ailments rates the same health-state as worse. Conclusion: Inequalities in self-reported ill-health cannot be attributed to positional objectivity; age, religion, state of residence, substance abuse, family type, dependents, and ailments impact individual health valuation.